Investigation of the Effect of Sedentary Life on the Health Status of Individuals - Erkan Cetinkaya, Erkan Şimşek, Ömer Zelyurt Mehmet Yasin Demirel (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Exercise is essential to the protection of the organism against disease, as well as its essential to a healthy life. In this study, the aim was to study the effects of inert life on human organism and to contribute to the quality of life of exercise. Methods: The method of the study is to compile all those who will contribute to our current work that has been scanned using the keywords ‘stationary life’, ‘exercise and health’, ‘protection of health’ in light of the studies in the relevant literature. Conclusion: In the study, it was concluded that immobile life has many negative aspects of the health of individuals, but also has a negative effect on individuals both physiologically and psychologically.